2010
DOI: 10.1021/la103468u
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of Quantum Dot Bioconjugates via Particle Lithography

Abstract: We present a simple technique to fabricate hexagonally ordered quantum dot bioconjugate (QDBC) dot arrays on glass coverslips. We used particle lithography to create periodic holes in a layer of methoxy-poly(ethylene glycol)-silane and then adsorbed QDBCs into the holes. To demonstrate the versatility of this technique, we made separate periodic arrays of quantum dots (QDs) conjugated to three different biologically important molecules: biotin, streptavidin, and anti-mouse IgG. The diameters of the regions whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…It has also been shown that such assemblies exhibited efficient quantum dot − quantum dot and quantum dot − dye energy transfer, which accommodated faster energy‐transfer rates as compared with densely packed quantum dot arrays placed on planar substrates. Taylor et al presented a simple approach to fabricate hexagonally ordered quantum dot bioconjugate (QDBC) arrays on glass coverslips. A particle lithography was used to create periodic holes on a layer of methoxy‐poly(ethylene glycol)‐silane and then have QDBCs adsorbed into the holes.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that such assemblies exhibited efficient quantum dot − quantum dot and quantum dot − dye energy transfer, which accommodated faster energy‐transfer rates as compared with densely packed quantum dot arrays placed on planar substrates. Taylor et al presented a simple approach to fabricate hexagonally ordered quantum dot bioconjugate (QDBC) arrays on glass coverslips. A particle lithography was used to create periodic holes on a layer of methoxy‐poly(ethylene glycol)‐silane and then have QDBCs adsorbed into the holes.…”
Section: Introductionmentioning
confidence: 99%
“…Positive or negative surface corrugations at the length scale of the assembled nanoparticles have been shown to effectively direct the particle positioning, , whereas self-assembled microparticle monolayers offer a convenient bottom-up template type for the massively parallel assembly of nanoscale objects. The concept of using larger microspheres was successfully applied earlier to create circular or localized patterns form quantum dots, quantum dot bioconjugates, or even gold nanoparticles. , These examples together with others, where the circular structures are formed directly from precursors in the liquid that was trapped beneath the microspheres, show that dewetting in a confined geometry can enable the preparation of circular structures from different materials. Unfortunately, due to the large number of parameters that determine the structure (e.g., template size, surface energies, speed of evaporation), unambiguous identification of the key parameters is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Protein patterns with micro- and nanometer scale features have been fabricated by a number of different techniques, including microfluidic patterning, photolithography, electron-beam lithography (EBL), , microcontact printing (μCP), dip-pen nanolithography (DPN), , and particle lithography. There are several factors to consider when choosing a technique for a specific application, including desired feature size and geometry, cost, processing time, and accessibility. Particle lithography is an attractive option to pattern protein because it relies on low cost, benchtop technology with the ability to produce nanostructured samples in parallel.…”
Section: Introductionmentioning
confidence: 99%